Laser Shock Processing of FCC Metals Mechanical Properties and Micro-structural Strengthening Mechanism - Zhang, Yongkang; Lu, Jinzhong; Luo, Kaiyu; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Laser shock processing (LSP) is a new and promising surface treatment technique for improving the fatigue durability, corrosion, wear resistance and other mechanical properties of metals and alloys. During LSP, the generated shock wave can introduce a deep compressive residual stress into the material, due to its high-pressure (GPa-TPa), ultra-fast (several tens nanoseconds), ultra-high strain-rate and high-energy. The overall properties and behavior of metal materials subjected to LSP were significantly improved because a refined surface layer was successfully obtained. Nevertheless, up to now, a clear scenery between micro-structure and macro-property of the refined surface layer, especially formation of sub-micrometer grains from coarse grains during severe plastic deformation, is still pending. Therefore, the basic studies of the underlying mechanism for grain refinement by ultra-high strain-rate presented in this book becomes more and more crucial.
Surface integrity of LY2 aluminum alloy subjected to laser shock processing -- Tensile properties and fatigue life of LY2 aluminum alloy by laser shock processing -- Grain refinement of the alloys with high stacking fault energy (SFE) induced by ultra-high plastic strain during multiple laser shock processing impacts -- Mechanical properties of ANSI 304 stainless steel subjected to laser shock processing -- Stress corrosion cracking (SCC) resistance of ANSI 304 austenitic stainless steel subjected to laser shock processing -- Grain refinement of the alloys with low stacking fault energy (SFE) induced by ultra-high plastic strain during multiple laser shock processing impacts -- Grain refinement of the alloys with medium stacking fault energy (SFE) induced by ultra-high plastic strain during multiple laser shock processing impacts.
Keywords: Structural control (Engineering).; Materials; Materials Science; Metallic Materials; Operating Procedures, Materials Treatment; Applied and Technical Physics